extent of implementation of lean manufacturing in industrial organizations A case study of the cement and derivatives corporation in chlef (Journal of Economic Additions, 2025)
This study aims to find out the extent of the application of lean manufacturing pillars in the cement enterprise in Chlef. To achieve this goal, the study adopted the descriptive and analytical analytical method, and the questionnaire was used as the main tool for data collection, where it was distributed to a sample of 58 individuals and 50 of them were returned. After analyzing the data using the statistical package SPSS 26 and testing the hypothesis,  the study found that there is an impact of applying the pillars of lean manufacturing in the sample institution, especially the organization of the work site, which received the highest percentage of agreement  among the members of the study sample with 86%, and the overall productive maintenance with 80%. The study recommended the need to educate workers to cooperate and participate in maintenance activities, as well as the need to accept the creative ideas presented by workers to improve production methods, in addition in addition to working on introducing more flexible equipment at the level of production.Jel Classification Codes: M11, L23
Keywords: Manufacturing systems; lean manufacturing; Industrial Organization; Strategie Management systems; Continuous Improvement